Evaluation of peripheral versus central effects of GABAB receptor activation using a novel, positive allosteric modulator of the GABAB receptor ADX71943, a pharmacological tool compound with a fully peripheral activity profile. (5th September 2014) - Kalinichev, M; Donovan‐Rodriguez, T; Girard, F; Riguet, E; Rouillier, M; Bournique, B; Haddouk, H; Mutel, V; Poli, S
<x xml:space="preserve">Abstract</x> Background and Purpose The GABAB receptor agonist, baclofen, has shown promising effects in patients suffering from pain, post‐traumatic stress disorder, alcoholism, overactive bladder and gastroesophageal reflux disease. However, baclofen's short duration of action and side effects limit its wider use. Here we characterized a novel, GABAB receptor positive allosteric modulator (PAM) ADX71943. Experimental Approach I n vitro, ADX71943 was assessed for pharmacological activity and selectivity using recombinant and native GABAB receptors. In vivo ADX71943 was assessed in the acetic acid‐induced writhing (AAW) test in mice and formalin tests (FTs) in mice and rats. Marble burying (MB) and elevated plus maze (EPM) tests, rotarod, spontaneous locomotor activity (sLMA) and body temperature (BT) tests in mice and rats were used to investigate centrally‐mediated effects. Key Results I n vitro, in the presence of GABA, ADX71943 increased the potency and efficacy of agonists and showed selectivity at the GABAB receptor. ADX71943 reduced pain‐associated behaviours in AAW; an effect blocked by GABAB receptor antagonist CGP63360. ADX71943 reduced pain in the FT in mice and rats, but was inactive in the MB and EPM despite reaching high concentrations in plasma. ADX71943 had no effect on BT, rotarod and sLMA. Conclusions and Implications ADX71943 showed consistent and target‐related efficacy in tests of disorders that have a significant peripheral component (acute and chronic pain), while having no effect in those associated with centrally‐mediated anxiety‐like reactivity and side effects. Thus, ADX71943 is a useful pharmacological tool for delineation of peripherally‐ versus centrally‐mediated effects of GABAB receptor activation.